MENJAGA SUMBER DAYA TANAH DENGAN KONSEP HOLISTIC AGRICULTURE SUSTAINABLE, INTEGRATED DAN SUSTAINABLE FARMING, GREEN AGRICULTURE TECHNOLOGY - Setiyo Budi, Agung; Imamal Khujjah, Fajriatul; Pujiati, Amin; Dian Wiska Pranjanti, Sucihartiningsih (Fakultas Pertanian, Program Studi Agroteknologi, 2024)
Sustainable agricultural development is a process aimed at always adding agricultural products to each consumer, while at the same time increasing acceleration, business productivity through the addition of skills and capital. The current implementation of development emphasizes the goal of economic progress. In essence, the concept of sustainable agricultural development has an integrated concept through a holistic approach. In the context of sustainable agricultural development, it basically means the ability to remain productive while maintaining resources. Agricultural development without any continuous effort, farmers will remain marginalized, trapped in debt, middlemen, and have no power to determine the economic value of the harvest. The impact of this is that the number of farmers will decrease, in the end Indonesian Food sovereignty will be difficult to achieve. Sustainable agricultural development through a holistic approach that is multidimensional from upstream to downstream. This article aims to provide new ideas in sustainable agricultural development through a holistic approach with the concept of holistic agriculture sustainable, integrated and sustainable farming, green agriculture technology from upstream to downstream as an effort to develop sustainable agricultural concepts and improve the welfare of farmers.